2020
DOI: 10.1186/s12903-019-0982-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of dental plaque reduction after use of electric toothbrushes with and without QLF-D-applied plaque visualization: a 1-week randomized controlled trial

Abstract: Background: To evaluate the efficacy of a newly developed electric toothbrush in reducing dental plaque via a quantitative light-induced fluorescence-digital (QLF-D)-applied visualisation system in the brush head. Methods: Participants included 20 adults aged 19 to 28 years. Participants were randomly assigned either (i) an electric toothbrush with a monitor to visualise red-fluorescent dental plaque via a camera built into the brush head (monitor usage group, n = 10) or (ii) an electric toothbrush without a m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 24 publications
0
5
0
3
Order By: Relevance
“…However, studies using the modified Oral Assessment Guide have shown that there are no differences in oral hygiene findings with different oral care methods [23,24,40]. In contrast, studies in which dental evaluation, such as plaque score, or objective evaluation, such as bacterial identification, were conducted have shown clear differences in results between various oral care methods, allowing for comparisons of the effects of oral care methods [41][42][43][44][45][46][47][48][49].…”
Section: Oral Hygiene Management Methods For Patients In Icusmentioning
confidence: 99%
See 1 more Smart Citation
“…However, studies using the modified Oral Assessment Guide have shown that there are no differences in oral hygiene findings with different oral care methods [23,24,40]. In contrast, studies in which dental evaluation, such as plaque score, or objective evaluation, such as bacterial identification, were conducted have shown clear differences in results between various oral care methods, allowing for comparisons of the effects of oral care methods [41][42][43][44][45][46][47][48][49].…”
Section: Oral Hygiene Management Methods For Patients In Icusmentioning
confidence: 99%
“…In 2018, Singh et al evaluated plaque using fluorescence photographs to compare the effects of two oral hygiene management methods [44]. In 2020, Akifusa et al reported that brushing while visualizing plaque in real time with QLF is very effective in plaque removal [43]. QLF technology can quantify bacterial lesions in the oral cavity to evaluate the oral health and visualize the effects of oral care in real time.…”
Section: Application Of Quantitative Light-induced Fluorescence Technologymentioning
confidence: 99%
“…Moreover, it promotes the exchange of recombinant plasmids. Once the ecosystem has been structured, it is almost impossible to change or destroy it, except through professional oral hygiene [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , ...…”
Section: Introductionmentioning
confidence: 99%
“…The same is true for Actiniomyces , but they colonize the subgingival surfaces of the tooth. These processes initiate the formation of dental plaque, which results in carious lesions [ 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ]. Sometimes the inhibition of colonization processes may stop.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation